Localizing Christopher Marlowe his life, plays and mythology, 1575-1593 - Ide, Arata (D.S. Brewer, 2023)
"This study punctures the stereotyped portrayals of Marlowe, first created by his rival Robert Greene, and, yet, which still colour our view. In doing so, Ide reveals the social and cultural discourses out of which such myths emerged. We know next to nothing about the life of the playwright Christopher Marlowe (b.1564 - d. 1593). Few documents survive other than his birth record in the parish register, a handful of legal cases in court records, Privy Council mandates and reports to the Council, the coroner's examination of his death, and a few hearsay accounts of his atheism. With such a limited collection of biographical documents available, it is impossible to retrieve from history a complete sense of Marlowe. However, this does not mean that biography cannot play a significant role in Marlowe studies. By observing the details of the specific places and communities to which Marlowe belonged, this book highlights the collective experiences and concerns of the social groups and communities with which we know he was personally and financially involved. Specifically, Localizing Christopher Marlowe reveals the political and cultural dynamics in the community of Corpus Christi College, Cambridge, into which Marlowe was deeply integrated and through which he became affiliated with the circle of Sir Francis Walsingham, mapping these influences in both his life and works
Keywords: Marlowe, Christopher / 1564-1593 / Criticism and interpretation; Dramatists, English / Early modern, 1500-1700 / Biography; Marlowe, Christopher / 1564-1593; Dramatists, English / Early modern / Biography; Engelska dramatiker; Tidigmodern tid; Storbritannien / England; Criticism, interpretation, etc; Biografier